Exploring the Influence of Green Brand on Consumers Purchase Intention for Eco-Friendly Lipstick - Nurjanah; Evi Maya Odelia (Jurnal Ilmu Manajemen, 2025)
This study aims to examine the influence of eco labels, consumer knowledge, and environmental awareness on the interest in buying eco-labeled lipsticks, with green brands as the mediating variable. This research is motivated by the increasing attention to sustainability issues in the cosmetics industry and changes in consumer behavior that increasingly consider environmental aspects in purchasing decisions. A quantitative approach was used in this study with the analysis of Partial Least Squares (PLS) with the help of SmartPLS software. Data was collected from 100 female respondents who had experience or interest in environmentally friendly cosmetic products. The results of the study show that green brands have a significant effect on buying interest. Environmental awareness also has a significant effect on buying interest, albeit in a negative direction. On the other hand, eco-labels and consumer knowledge have no direct effect on buying interest. In indirect relationships, green brands have been proven to mediate the influence of consumer knowledge on buying interest, but do not mediate the influence of eco-labels and environmental awareness. These findings suggest that strengthening green brand image has a more important role in influencing purchasing decisions than just the presence of the label or the level of consumer knowledge and awareness. This research provides implications for cosmetics companies to emphasize sustainable branding strategies to increase product appeal in a market that is increasingly concerned about the environment.